Airway microbiome research: a modern perspective on surveillance cultures? - Roux, Damien; Oort, Pouline M. van; Ricard, Jean-Damien; Bos, Lieuwe D. J. (Annals of Translational Medicine, 2017)
The incidence of ventilator-associated pneumonia (VAP) is estimated to be around 10% in a high-risk population. Over the last decade, major improvements have been made in the prevention of VAP, with great cost-effectiveness. However, we still do not understand the exact pathogenesis of VAP. A better understanding might explain why some patients develop ventilator-associated tracheobronchitis, while others develop VAP even though they are infected with the same types of pathogens. Microbiome research has been a hot topic in translational medicine over the past decade. Slowly, microbiome research has also been introduced to the intensive care setting. One of the areas where it may influence our pathophysiological considerations is in VAP. The adapted island has been proposed for the colonization and infection of the respiratory tract. In this model, not only the immigration of bacteria into the lung is important, but elimination and regional growth factors are of equal significance. The importance of these factors can be supported by epidemiological studies. Several small observational studies on the development of the pulmonary microbiome during mechanical ventilation also support this theory. We speculate on the consequences of the newest insights in microbiome research on the prevention and targeted treatment of VAP. We conclude that there is still a strong need for more in-depth analyses of the changes in the microbial composition of the pulmonary microbiome during mechanical ventilation and with the development of VAP.